Documents on the Nineteenth Century United Kingdom Constitution.
1 online resource (xvi, 128 pages)
Keywords: This volume considers the UK as a state that was both internally differentiated and placed a premium on its external relations and world power. It contains documents dealing with the implications of the multinational status of the UK. They relate to matters including discussions over the status of Ireland; and the constitutional position of the other nations of the UK. The volume also contains documents connected to the constitutional implications of the Empire, including the way in which it was managed, and how should be structured. It contains material relevant to the constitutional impact of the UK on the outside world.